Comparative study between fast terminal and second order sliding mode controls applied to a wind energy conversion system - Touati Abdelwahed; Majdoul Radouane; Taouni Abderrahim; Mohamed Aboulfatah; Rabbah Nabila (Indonesian Journal of Electrical Engineering and Computer Science, 2021)
A he wind energy conversion system (WECS) consists of many subsystems, which present control difficulties due to the strong nonlinearities of the models and the effects of internal or external disturbances. In this work, the WECS is based on a doubly feed induction generator (DFIG) directly connected to the stator side network and interconnected via a power converter on the rotor side. The aim of the control strategy is to achieve regular regulation of the powers supplied by the generator and to produce energy of better quality. in order to improve the dynamic behavior of the doubly fed induction generator (DFIG); a comparative study is presented between two advanced control strategies; the second order sliding mode control and the FTSMC fast terminal sliding mode control. The proposed advanced tracking controller is synthesized based on the Lyapunov stability theory and guarantees the existence of the sliding mode around the sliding surface in a finite time. The analysis of the simulation results under the Matlab/Simulink environment confirms the effectiveness of the proposed methods through the performances obtained.